2015
DOI: 10.18632/oncotarget.4980
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism inADIPOQpredicts biochemical recurrence after radical prostatectomy in localized prostate cancer

Abstract: Adiponectin has been implicated in prostate cancer (PCa) aggressiveness. However, the role of genetic variations in the adiponectin (ADIPOQ) gene in PCa progression remains unknown. To determine whether genetic variants in ADIPOQ are associated with the risk of biochemical recurrence (BCR) after radical prostatectomy (RP). We evaluated three common ADIPOQ polymorphisms in 728 men with clinically localized PCa who underwent RP. Multivariable Cox proportional hazards models and Kaplan–Meier analysis were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
(46 reference statements)
0
9
0
3
Order By: Relevance
“…We retrospectively analyzed 738 men who had undergone RP from 2 independent cohorts in China as described previously. [ 19 ] The 1st cohort was composed of 312 patients from the Affiliated Hospital of Qingdao University and Fudan University Shanghai Cancer Center, and the 2nd was composed of 426 patients from Fudan University Shanghai Cancer Center. The median follow-up times were 36.3 and 37.7 months.…”
Section: Methodsmentioning
confidence: 99%
“…We retrospectively analyzed 738 men who had undergone RP from 2 independent cohorts in China as described previously. [ 19 ] The 1st cohort was composed of 312 patients from the Affiliated Hospital of Qingdao University and Fudan University Shanghai Cancer Center, and the 2nd was composed of 426 patients from Fudan University Shanghai Cancer Center. The median follow-up times were 36.3 and 37.7 months.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, genetic markers among cancer patients appears have been increasingly investigated. To date, several promising polymorphisms have not been used to screen for prostate cancer or incorporate into nomograms to predict patient survivals, however, may provide potential useful information to optimize the diagnosis, therapy and follow-up of patients with prostate cancer 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The study subjects were mostly from previously published case-control study 7 . Briefly, 1115 eligible patients recruited into this study were newly diagnosed and histopathologically confirmed primary prostate adenocarcinoma from Fudan University Shanghai Cancer Center (FUSCC) between January 2005 and January 2012, of whom 1015 (92%) agreed to participate in this study.…”
Section: Methodsmentioning
confidence: 99%